Relationship of individual psychological factors of cadets’ adaptation in voyage conditions - O. Ivanova; Y. Chumaieva; S. Kushchinska (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The relevance of the study is conditioned by the need to update data on the specifics of the activities of cadet sailors due to rapid changes in the organisational structure of modern society and understanding the role of this profession in it. The purpose of the study was to reveal the psychophysiological and individual psychological determinants of adaptation and their interdependence in the context of professional activity of novice seafarers. The paper uses methods of theoretic and methodological analysis, psychodiagnostic survey, and Pearson’s correlation analysis methods. As a result of the theoretical analysis, four groups of factors of professional adaptation were identified: psychophysiological, individual and psychological, socio-psychological, organisational and structural. Based on these factors, an empirical study was organised, which revealed the relationship between indicators of psychological stability, self-confidence, adaptability, and tolerance to ambiguity. It was determined that psychological resilience is associated with the parameters of passion, resourcefulness, optimism, and the level of expression of motivational components of professional activity of cadets, determined by the motives of life support and self-realisation. Disturbances in health, in particular in terms of exhaustion, emotional and vegetative instability, anxiety and fears, and maladjustment, affect the effectiveness and quality of value, emotional, volitional, social and informational regulation. The most common symptoms of health disorders among cadets on a voyage are vegetative and emotional instability, sleep disturbances, less pronounced symptoms of maladjustment such as addictions, anxiety, and fears, and the least pronounced symptoms are psychophysical exhaustion and willpower disorders. The paper contributes to the psychological science of professional and personal adaptability of the individual in extreme conditions. The study is of practical value for sociologists, teachers, psychologists, psychotherapists and doctors, who can contribute to solving problems of maladaptation in the labour sphere